Life and Agency: Constitutivism and the Source of Prescriptive Norms - (:unkn) unknown (My University, 2015)
I explore a recent project in metaethics known as "constitutivism," and presents an outline of a new approach to that view. Constitutivism is an approach to moral realism that attempts to ground objective moral norms in the nature of action. This is done by showing that action has a constitutive aim, and that agents are committed to action, and so are thereby committed to that aim. Since agents can fulfill that aim with varying degrees of success, this aim generates a standard of evaluation. If this project succeeds, it would serve to make moral norms real and objective and simultaneously avoid the serious epistemological or metaphysical obstacles that traditional realism faces. This view has come under criticism from philosophers who argue that the norms deriving from the nature of action will be insufficient to deal with moral skepticism and will be arbitrary from a normative point of view. I outline a form of neo-Aristotelian constitutivism that I think does not face these problems.We can conceive of action in both a minimal and substantive way, and that a substantive conception of action generates objective norms when coupled with important considerations about the biological nature of human beings. Finally, I discuss the crucial role of choice in my view of morality and the objectivity of norms.
Keywords: Action Theory; Analytic Philosophy; Ethics; Metaethics